PENGALAMAN DALAM PELAKSANAAN KLINIK BERHENTI MEROKOK DI KOTA DENPASAR: EXPERIENCE IN IMPLEMENTING THE SMOKING CESSATION CLINIC IN DENPASAR - Prihatiningsih, Diah; Purwanti, Ika Setya; Devhy, Ni Luh Putu (Bali Medika Jurnal, 2019)
One habit that is commonly practiced by two out of three adult men in Indonesia is smoking, but this behaviour has the potential to cause chronic diseases. The Indonesian government has made various efforts to reduce the number of smokers in Indonesia. One of the efforts is to establish a Smoking Cessation Clinic in primary and referral health care facilities. This study uses qualitative research methods with descriptive phenomenological approach. This research was conducted in 4 smoking cessation clinics in Denpasar; Puskesmas I Denpasar Utara, Puskesmas I Denpasar Barat, Puskesmas I Denpasar Selatan, and Puskesmas I Denpasar Timur. Based on interviews and observations conducted by 4 respondents/participants, 3 big themes were founded, they were experience of the smoking cessation program in Denpasar, obstacles during the implementation of the smoking cessation clinic and suggestions for improving the implementation of the smoking cessation clinic. Participants perceive their understanding of the implementation of the smoking cessation clinic as a means to attract smokers who come to the Puskesmas for medical treatment and are then given information about the existence of a smoking cessation program. In this program counselling is given about the dangers of smoking so they want to stop smoking. The difficulties pf implementating the smoking cessation clinic is the lack of people who are willing to come to the smoking cessation clinic, a need to socialize the existence of a smoking cessation clinic and redirecting those who went to other polyclinics to visit the smoking cessation clinic. Keywords : Smoke, Smoking Cessation Clinic